2017
DOI: 10.1371/journal.pone.0187829
|View full text |Cite
|
Sign up to set email alerts
|

Male group size, female distribution and changes in sexual segregation by Roosevelt elk

Abstract: Sexual segregation, or the differential use of space by males and females, is hypothesized to be a function of body size dimorphism. Sexual segregation can also manifest at small (social segregation) and large (habitat segregation) spatial scales for a variety of reasons. Furthermore, the connection between small- and large-scale sexual segregation has rarely been addressed. We studied a population of Roosevelt elk (Cervus elaphus roosevelti) across 21 years in north coastal California, USA, to assess small- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…This problem is further complicated by additional unmodeled sources of heterogeneity in resource selection patterns. Prior work has demonstrated that heterogeneity in movement patterns arises from differences among populations, sex, and ecological dynamics (e.g., variation induced by density‐dependent process or predation; Anderson et al, 2005 ; McCorquodale, 2003 ; McLoughlin et al, 2010 ; Peterson & Weckerly, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This problem is further complicated by additional unmodeled sources of heterogeneity in resource selection patterns. Prior work has demonstrated that heterogeneity in movement patterns arises from differences among populations, sex, and ecological dynamics (e.g., variation induced by density‐dependent process or predation; Anderson et al, 2005 ; McCorquodale, 2003 ; McLoughlin et al, 2010 ; Peterson & Weckerly, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The herds were habituated to people, and so all observations were carried out within 200 meters of elk using binoculars or the naked eye. We did not include adult males because they do not graze the Davison meadow complex to the same degree as female herds [35,36]. We used the highest count across the 10 surveys as our estimate of population abundance for each year.…”
Section: Weather and Elk Abundancementioning
confidence: 99%
“…Coastal redwood (Sequoia sempervirens), Douglas-fir (Pseudotsuga menziesii), Sitka spruce (Picea sitchensis), and Western hemlock (Tsuga heterophylla) were among the most abundant tree species in the study area. Boyes meadow complex is 70 ha in size and Davison meadow complex lies approximately two km away and is 51 ha in size (Peterson & Weckerly, 2017). The meadow complexes had flat terrain and were dominated by annual and perennial grass species such as California oatgrass (Danthonia californica), redtop (Agrostis gigantean), soft chess (Bromus hordeaceus), and reed canary grass (Phalaris arundinacea) (Weckerly et al, 2001;Starns et al, 2015).…”
Section: Study Areamentioning
confidence: 99%
“…Bites taken were counted during the focal observation and cropping rate was (the number of bites taken)/(focal observation length). Sex, age class of the focal elk, and group type (male in a male-only group, females in female group, male in female group, and juveniles in female group) were recorded to capture any potential influences these factors might have on cropping rate (Townsend & Bailey, 1981;Weckerly, 2001;Peterson & Weckerly, 2017). Males were included in two group types to assess if their behaviours varied when grouped with females because males are socially dominant to females.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation